Anticoagulation in splanchnic and cerebral vein thrombosis: An international vignette‐based survey. Issue 7 (11th September 2020) - Riva, Nicoletta; Carrier, Marc; Gatt, Alex; Ageno, Walter
Abstract: Background: Anticoagulant treatment of splanchnic (SVT) and cerebral vein thrombosis (CVT) can be challenging due to the rarity of these conditions, the concomitantly high thrombotic and bleeding risks, and the available low‐quality evidence. Objectives: To explore the current therapeutic approaches to SVT and CVT, and the rationale behind the anticoagulant treatment choice. Methods: A cross‐sectional survey was conducted (October 2018‐April 2019) among members of three thrombosis and hemostasis societies. The survey consisted of four vignette cases: (i) SVT secondary to transient risk factor; (ii) cirrhotic SVT with esophageal varices; (iii) CVT secondary to transient risk factor; and (iv) unprovoked CVT with intracranial hemorrhage. Results: A total of 397 physicians responded to the survey. There was wide variability in anticoagulant treatment options, starting time, and duration. Vitamin K antagonists were the commonest choice across the four vignette cases (44.2%‐63.0%). The direct oral anticoagulants (DOACs) were the second commonest choice in low‐bleeding‐risk scenarios (27.7% in case 1, 22.9% in case 3), while parenteral anticoagulation alone was the second commonest choice in high‐bleeding‐risk scenarios (39.9% in case 2, 39.8% in case 4). The most frequent reasons for selecting DOACs were oral route of administration (50.6%), lack of need for laboratory monitoring (48.1%), and favorable safety profile of these drugs (43.4%). Conclusions: The results of our study showed that, despite being off‐label, the DOACs were considered for the treatment of unusual‐site venous thromboembolism. The wide variability among different physicians reflected the clinical difficulties and raised the need for more collaborative trials on these disorders.